Electrical stimulation of the ventral tegmental area restores consciousness from sevoflurane-, dexmedetomidine-, and fentanyl-induced unconsciousness in rats - Kathleen F. Vincent; Edlyn R. Zhang; Angel J. Cho; Risako Kato-Miyabe; Olivia G. Mallari; Olivia A. Moody; David P. Obert; Gwi H. Park; Ken Solt (Brain Stimulation, 2024)
Background: Dopaminergic neurons in the ventral tegmental area (VTA) are crucially involved in regulating arousal, making them a potential target for reversing general anesthesia. Electrical deep brain stimulation (DBS) of the VTA restores consciousness in animals anesthetized with drugs that primarily enhance GABAA receptors. However, it is unknown if VTA DBS restores consciousness in animals anesthetized with drugs that target other receptors. Objective: To evaluate the efficacy of VTA DBS in restoring consciousness after exposure to four anesthetics with distinct receptor targets. Methods: Sixteen adult Sprague-Dawley rats (8 female, 8 male) with bipolar electrodes implanted in the VTA were exposed to dexmedetomidine, fentanyl, ketamine, or sevoflurane to produce loss of righting, a proxy for unconsciousness. After receiving the dopamine D1 receptor antagonist, SCH-23390, or saline (vehicle), DBS was initiated at 30 μA and increased by 10 μA until reaching a maximum of 100 μA. The current that evoked behavioral arousal and restored righting was recorded for each anesthetic and compared across drug (saline/SCH-23390) condition. Electroencephalogram, heart rate and pulse oximetry were recorded continuously. Results: VTA DBS restored righting after sevoflurane, dexmedetomidine, and fentanyl-induced unconsciousness, but not ketamine-induced unconsciousness. D1 receptor antagonism diminished the efficacy of VTA stimulation following sevoflurane and fentanyl, but not dexmedetomidine. Conclusions: Electrical DBS of the VTA restores consciousness in animals anesthetized with mechanistically distinct drugs, excluding ketamine. The involvement of the D1 receptor in mediating this effect is anesthetic-specific.